Superflex: Innovative Learning to Develop Social Attitude Competencies - Rachmah, Huriah; Gunawan, Rudy; Hendrawan, Jajang Hendar (International Journal of Elementary Education, 2018)
The 2013 curriculum aims to produce students to have three competencies: attitude, knowledge and skills.  Competence of attitude is divided into two, namely spiritual and social. Competence of social attitude is done during the learning process and assessment. But not on all subjects, the process and attitude assessment is done by the teacher. Assessment of attitudes in primary schools is done by classroom teachers, teachers of religious instruction lessons, PJOK, and extracurricular coaches. Social attitude is an integral part of social thinking because attitude is the fruit of thought. Learning Superflex® is a model developed in 2008 in the United States and in this research is adapted to help address issues related to social attitudes. This research uses descriptive analysis method. Some of the data is taken from the results of research that the author did and still runs until this year. The data is collaborated with the data obtained from the literature to produce this study. The conclusion of this study that innovative learning model depends on the creativity of teachers in generating motivation learners. The Superflex® learning model can be an inspiration for teachers as one of the innovative learning models that can build students' social attitudes.